Life-Cycle Cost Model and Design Optimization of Base-Isolated Building Structures - Mitropoulou, Chara Ch.; Lagaros, Nikos D. (Frontiers in Built Environment, 2016)
Design of economic structures adequately resistant to withstand during their service life, without catastrophic failures, all possible loading conditions and to absorb the induced seismic energy in a controlled manner, was subjected to intensive research so far. Costly and extremely sensitive equipment, vital in commerce, business, education, and/or health care represent the contents of the contemporary structural systems. Frequently, structures themselves are less valuable than their contents. Moreover, following a catastrophic natural disaster, local communities requires that communication and emergency centers, hospitals, police, and fire stations to be fully operational. In conventional constructions, high floor accelerations are encountered in case of stiff buildings or large interstory drifts in flexible ones. These structural performance characteristics cause difficulties in protecting both building and its contents. As an efficient alternative design practice, base-isolated structures are considered, compared to the conventional fixed-base one. A critical evaluation of optimized fixed and base-isolated reinforced concrete buildings is performed in this study, with respect to the initial and total cost taking into account the life-cycle cost.